A Systematic Review and Meta-analysis of Robotic Gripper. Issue 4 (March 2020) - Long, Zhang; Jiang, Qian; Shuai, Tao; Wen, Feijuan; Liang, Chunping
Abstract: With the rapid development of robotics, robots gradually replace people to complete various tasks. Grasping is one of the most common tasks in industry and daily life. In addition to typical pick-and-place task, grasping a tool is the basis for performing other tasks, such as grabbing the key to open the door, grabbing a hammer to nail, etc. The robotic grippers are the manipulator in which the robot completes the grasp. Their performance characteristics have a significant impact on work efficiency because they are the parts interacting with the grasping objects directly. Therefore, this paper researches on robotic gripper and its related technology from the following aspects. First of all, the current robotic gripper type is analyzed in detail. Second, the research status of the most promising robotic gripper is reviewed widely. Third, the critical technology of robotic gripper is studied deeply. Finally, the analysis of robotic gripper development trend is performed prospectively.